DEVELOPMENT OF SCIENCE-BASED DIGITAL POP-UP BOOKS: A CREATIVE SOLUTION FOR ELEMENTARY SCHOOL STUDENTS' LEARNING - Yoyo Zakaria Ansori; Devi Afriyuni Yonanda; Budi Febriyanto; Vycka Ramandhita; Saepul Anwar (Universitas Majalengka, 2024)
The development of digital technology in the 21st century has encouraged innovation in learning strategies that are more engaging and focused on active student participation. This study aims to design and develop an interactive learning medium in the form of a digital pop-up book focused on the subject of Natural Sciences (IPA) for fifth-grade elementary school students, with the main topic being the water cycle. The development of the medium was based on the ADDIE instructional design model, which includes five stages: needs analysis, concept design, product development, classroom implementation, and evaluation of the medium's effectiveness and practicality. The digital pop-up book was created using Microsoft PowerPoint software by combining various three-dimensional visual elements, dynamic animations, voice narration, and interactive features that facilitate students' understanding of concepts. Validation results from experts showed a very high level of feasibility, namely 88% from subject matter experts and 93.3% from media experts. Meanwhile, the practicality test results by teachers and students each scored 95% and 93%, indicating that this media is very easy to use in daily learning. In addition to feasibility and practicality, the effectiveness of the media was also tested through a comparison of scores before and after using the media, showing a significant improvement in student learning outcomes. The average N-Gain score reached 79.06%, which falls into the high or effective category. Based on these results, this digital pop-up book can be concluded as a learning medium that is not only feasible and practical but also capable of having a positive impact on enhancing students' conceptual understanding and learning interest in elementary schools.